2015
DOI: 10.1111/1753-6405.12441
|View full text |Cite
|
Sign up to set email alerts
|

The portrayal of mental health in Australian daily newspapers

Abstract: Objective: To examine how mental health is portrayed as a holistic construct in three major Australian daily newspapers. Methods:Using an unobtrusive, mixed methods approach incorporating content and thematic analyses, data were collected from hard copies of The Age, The Australian and Herald Sun newspapers and their weekend counterparts over 12 weeks in 2012.Results: Newspaper coverage of mental health favoured stories about illness over wellbeing. While the issue was typically reported responsibly, psychotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 17 publications
0
21
0
3
Order By: Relevance
“…Such efforts have been largely driven by initiatives aiming to improve media reporting of suicide [38,39]. A recent analysis of the portrayal of mental health in Australian daily newspapers showed that, while newspaper coverage of mental health favoured stories about illness over wellbeing, the issue was typically reported responsibly and positive mental health messages were common [40]. However, psychotic disorders were overrepresented in discussions of illness and were often discussed in relation to criminal behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Such efforts have been largely driven by initiatives aiming to improve media reporting of suicide [38,39]. A recent analysis of the portrayal of mental health in Australian daily newspapers showed that, while newspaper coverage of mental health favoured stories about illness over wellbeing, the issue was typically reported responsibly and positive mental health messages were common [40]. However, psychotic disorders were overrepresented in discussions of illness and were often discussed in relation to criminal behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested in previous studies, 9,13–15 there is a need for a better collaboration between cycling safety advocates and media professionals, perhaps through combined workshops and other training opportunities, to improve the coverage of cyclist crashes. There is also a need for leadership from high‐level management of major newspapers to promote among their staff more balanced reporting of bicycle crashes with a focus on injury prevention.…”
Section: Discussionmentioning
confidence: 95%
“…Recent Australian research has investigated media representation of obesity and mental illness, 27,28 but to our knowledge, ours is the first to examine the language used by the media when communicating about diabetes in Australia. Overall, there was a significant increase in articles including preferred language in 2014 as compared to 2010.…”
Section: Discussionmentioning
confidence: 99%